Mechanical properties of ceramics and composite resins - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
We investigated the mechanical properties of certain dental restorative materials to assess their durability. This study determines the flexural strength of a ceramic material (Finesse(TM), Dentsply), a hybrid ceramic resin (Estenia(TM), Kuraray), an ormocer (Admira(TM), Voco) and a posterior composite resin (Solitaire2(TM), Heraeus Kulzer). The specimens were fabricated from the various restoratives. Flexural strength was determined in 4-point bending. Scanning electron microscopy (SEM) was used to examine and compare surface topography of the fractured and nonfractured surfaces. The results were analyzed statistically. The flexural strength values of Estenia(TM) samples were significantly higher compared to those of Admira(TM) and Finesse(TM) (p<0.006).
Keywords: ceramic materials; posterior composite resins; hybrid composite resin; flexural strength